Clinical and professional reasoning in occupational therapy - Schell, Barbara A. Boyt; Schell, John W. (John William) 1947- (Wolters Kluwer, 2018)
Schell & Schell's Clinical and Professional Reasoning in Occupational Therapy, 2nd Edition offers up-to-date, easy-to-understand coverage of the theories and insights gained from years of studying how occupational therapy practitioners reason in practice. Written by an expanded team of international educators, researchers and practitioners, the book is the only work that goes beyond simply directing how therapists should think to exploring whyand how they actually think the way they do when working with clients. The 2nd Edition offers a wide array of new chapters and a new, more focused four-part organization that helps Occupational Therapy students develop the skills they need to identify and solve challenges throughout their careers. Reorganized text to focuses on theories and examples of professional reasoning in practice. New chapters in Unit I include a detailed description of Schell's Ecological Model of Professional Reasoning and a new chapter on Embodiment. Unit II includes a new chapter on Aspects of Reasoning and an expanded chapter on Interactive Reasoning. A brand new Unit III on Professional Reasoning in Context shares actual cases and outlines the nuances of reasoning in different practice settings ranging from the NICU to community mental health. Unit IV includes new and updated chapters on teaching in higher education and fieldwork, a new chapter on professional reasoning in management, and a revised chapter on considerations in research and scholarship in professional reasoning. Thinking About Thinking boxes are threaded throughout Learning activities in each chapter that ask readers to use different kinds of reasoning to manage various occupational therapy scenarios.Case Examples demonstrate how effective reasoning is applied in handling a range of clinical and professional issues"--